Ethnic comparison in takotsubo syndrome: novel insights from the International Takotsubo Registry - Imori, Yoichi; Kato, Ken; Cammann, Victoria L; Szawan, Konrad A; Wischnewsky, Manfred; Dreiding, Sara; Würdinger, Michael; Schönberger, Maximilian; Petkova, Vanya; Niederseer, David; Levinson, Rena A; Di Vece, Davide; et al. (Clinical research in cardiology, 2022)
BACKGROUND: Ethnic disparities have been reported in cardiovascular disease. However, ethnic disparities in takotsubo syndrome (TTS) remain elusive. This study assessed differences in clinical characteristics between Japanese and European TTS patients and determined the impact of ethnicity on in-hospital outcomes. METHODS: TTS patients in Japan were enrolled from 10 hospitals and TTS patients in Europe were enrolled from 32 hospitals participating in the International Takotsubo Registry. Clinical characteristics and in-hospital outcomes were compared between Japanese and European patients. RESULTS: A total of 503 Japanese and 1670 European patients were included. Japanese patients were older (72.6 ± 11.4 years vs. 68.0 ± 12.0 years; p < 0.001) and more likely to be male (18.5 vs. 8.4%; p < 0.001) than European TTS patients. Physical triggering factors were more common (45.5 vs. 32.0%; p < 0.001), and emotional triggers less common (17.5 vs. 31.5%; p < 0.001), in Japanese patients than in European patients. Japanese patients were more likely to experience cardiogenic shock during the acute phase (15.5 vs. 9.0%; p < 0.001) and had a higher in-hospital mortality (8.2 vs. 3.2%; p < 0.001). However, ethnicity itself did not appear to have an impact on in-hospital mortality. Machine learning approach revealed that the presence of physical stressors was the most important prognostic factor in both Japanese and European TTS patients. CONCLUSION: Differences in clinical characteristics and in-hospital outcomes between Japanese and European TTS patients exist. Ethnicity does not impact the outcome in TTS patients. The worse in-hospital outcome in Japanese patients, is mainly driven by the higher prevalence of physical triggers. TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique Identifier: NCT01947621.
Keywords: Shock, Cardiogenic; Health Status Disparities; Japonsko; Hospital Mortality; Humans; Prevalence; běloši; disparity zdravotního stavu; lidé středního věku; Middle Aged; Europe; Asian People; mortalita v nemocnicích; Registries; mužské pohlaví; Evropa; kardiogenní šok; registrace; ženské pohlaví; takotsubo kardiomyopatie; White People; lidé; prevalence; Takotsubo Cardiomyopathy; Aged; Asijci; senioři; Male; Japan; Female